A Comparative Study in Health Habits and Attitudes of Students of Muscat and Dhofar in the Sultanate of Oman - Saead S. Al - Dhafri; Abdullah K. Ambusaidi (Sultan Qaboos University, 2013)
This study examined the possible differences in health attitudes and habits between Omani students from Muscat school district (north Oman) and students from Dhofar school district (south Oman). The participants responded to a group of questionnaires that included: health problems, weight satisfaction, attitudes towards physical activities, health and food habits, and attitudes towards and use of harmful substances. The sample consisted of 450 randomly selected middle and high school students. Independent t-tests and Chi-squares were used to answer the study questions. The results showed statistically significant differences in the levels of health problems, attitudes towards physical activities, frequency of eating fast food and hours of watching TV. Students from Muscat had more helath problems, revealed positive attitudes towards physical activities and more frequently eat fast food. No differences were found in weight satisfaction in the two school districts. Student of Dhofar showed higher tendency to use harmful substances than Muscat students did. Evidence was shown for a moderate consumption of fruit and vegetables among all participants, low consumption of soft drinks, of walking habits, low levels of physical activities, and few hours of computer use (with no differences between the two districts in any of these habits).